Challenging Perceptions of "Straight": Heterosexual Men Who Have Sex with Men and the Cultural Politics of Sexual Identity Categories. (October 2019) - Persson, Asha; Newman, Christy E.; Manolas, Pene; Holt, Martin; Callander, Denton; Gordon, Tina; de Wit, John
Research shows that some heterosexually identified men engage in sex with men; however, they remain largely hidden and little understood. Despite long-standing scholarly recognition that sexual identity and orientation do not always neatly coincide, the culturally normative heterosexual/homosexual binary tends to shape mainstream perceptions of such men as well as render them invisible in sexual health systems reliant on stable sexual identity categories. This invisibility, in turn, perpetuates the fiction of the binary. We explore perspectives on heterosexually identified men who have sex with men, drawing on recent research literature and on qualitative interviews with "key informants" in the Australian sexual health field who have frontline knowledge of these men. We consider the limitations of inventing a label to "encapsulate" these diverse men but also the significance of finding a language that meaningfully acknowledges their sexual realities and highlights heterosexuality as more varied and fluid than social attitudes and traditional sexual identity categories permit.